(3GdeSFhdjI GdeOfjI dEOGQI GdeSJTai Yf GdNWC GdWHj ddYGedjf ajgG (B:s ((3OQGSI ebGQfI(B) /s - (3eMSf, SejQI MSjfs ((3GdefUhQI, eUQ (B:s (3OGQ GdacQ hGdbGfhf ddfTQ hGdJhRjY,s, 2016)
(3jJfGhd cJGH (B((3GdeSFhdjI GdeOfjI dEOGQI GdeSJTai Yf GdNWC GdWHj ddYGedjf ajgG (B: ((3OQGSI ebGQfI(B)) (3hGdPj bGe HJCdjag (B((3SejQI MSjf eMSf(B) (3aj MhGdj (B(366) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdeSFhdjI GdeOfjI ddCWHGA(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3eGgjI GdYed GdWHj hGdWHjYjI GdbGfhfjI deSDhdjI EOGQI GdeSJTai Yf GdNWC GdWHj ddYGedjf ajgG, GdHGH GdKGfj (B: (3GdEWGQ GdbGfhfj ddeSDhdjI GdeOfjI dEOGQI GdeSJTai(B.s
(3HHdjhLQGajI (B: (3UaMI (B325-362.s
Keywords: (3GdeSJTajGJs -- (3bhGfjf hJTQjYGJs; (3GdeSFhdjI GdeOfjI ddCWHGAs